Open access and editorial quality control (2019)
Publishing is an enduring profession that has undergone series of metamorphic changes over time. Of unique impact is the innovative prowess and ingenuous mobility which technology has brought into publishing. The journey from traditional to electronic publishing had been gradual but that of electronic has been swift and accelerative. The latest in the trend is Open Access (OA) which is facilitated by the technological cohesiveness of computer and internet. Open access is the current academic trend which permits nearly an unfettered access to published articles by numerous enthusiastic users. Open Access publishers are many just as its patronage is teeming. With the prevalence and ubiquitousness of OA, one cannot but be agitated by the issue of quality of publications which is a sine qua non to effective knowledge transmission and academic growth. This paper discusses the issue of quality control in Open Access under six sub-headings, namely: introduction, overview of Open Access, Concept of editing, Total Quality Management, OA quality control, and conclusion.